Consumer Satisfaction with Telerehabilitation Service Provision of Alternative Computer Access and Augmentative and Alternative Communication - LoPresti, Edmund F.; Jinks, Andrew; Simpson, Richard C. (International Journal of Telerehabilitation, 2015)
Telerehabilitation (TR) services for assistive technology evaluation and training have the potential to reduce travel demands for consumers and assistive technology professionals while allowing evaluation in more familiar, salient environments for the consumer. Sixty-five consumers received TR services for augmentative and alternative communication or alternative computer access, and consumer satisfaction was compared with twenty-eight consumers who received exclusively in-person services. TR recipients rated their TR services at a median of 6 on a 6-point Likert scale TR satisfaction questionnaire, although individual responses did indicate room for improvement in the technology. Overall satisfaction with AT services was rated highly by both in-person (100% satisfaction) and TR (99% satisfaction) service recipients.